Evaluation of the economic costs of beach erosion due to the loss of the recreational services of sandy beaches - The case of Tetouan coast (Morocco). (October 2021) - Flayou, Latifa; Snoussi, Maria; Raji, Otmane
Abstract: Coastal managers and investors are increasingly aware that seaside tourism can only be sustainable if the coastal natural assets, in particular sandy beaches, are protected from erosion. Tetouan coast, which relies heavily on tourism is experiencing strong retreat. This study aims to value the lost profits to the tourism sector, if Tetouan beaches were to disappear. We also analyzed the costs of beach nourishment as erosion control measure. Through the integration of physical and economic simulations, the findings showed that beach erosion would have significant negative economic impacts on the tourism sector, and it will cost much more than the continuous control by artificial recharging, provided the availability of sand stocks. The study highlights the benefits of using economic valuation to promote investment in conservation and restoration measures, that maintain beach width and sustainably secure tourism business and the livelihoods of coastal communities. Highlights: Beach erosion is threatening the economic growth of Tetouan seaside tourism. Physical and economic assessment methods have been applied. Beach nourishment is economically efficient measure avoiding tourism losses.